Analysis of the Productivity of Land Resources of Crop Production Industries in the System of Sustainable Development Requirements - A. I. Belousov; G. V. Mikhailova (Наука. Инновации. Технологии)
Introduction. The article discusses issues related to the actualization of the problem of obtaining environmentally friendly products in the context of the requirements of sustainable development and the growing shortage of food. The basis for increasing the level of sustainability in agriculture should be the processes of gross savings of the productivity potential of land resources. From these positions, it is necessary to integrate environmental management indicators into the system of assessing the total capital of economic entities operating at the grassroots territorial level.Materials and methods of research. Through the use of balance generalizations, a specialized system of coefficients, cartographic surveys, the importance of strict compliance with the normative approach in assessing the parameters of productivity of land resources, both in terms of their artificial and organic support, is shown.Results. Using modeling procedures, variants of nutrient recovery in the soil are presented, which made it possible to form a block model of the forecast of agricultural nature management, focused on the need for capital increment and, above all, in terms of its land form.Conclusions. The use of such a model makes it possible to conclude that it is necessary to increase the integrating importance of territorial environmental protection bodies, which should be focused on an integrated system of monitoring the state of land resources, allowing to increase the synergetic role of information flows of grassroots economic and territorial entities.